Stakeholder Relationships And Sustainability The Case Of Health Aid To The Kyrgyz Republic - Isabekova, Gulnaz (Global Dynamics of Social Policy,, 2024)
This open-access book analyses how stakeholder relationships impact the sustainability of health aid. It does this by providing an overarching analytical framework, which allows for a systematic analysis of sustainability, relationships, and a possible causal link between these phenomena. The book goes beyond universal paradigms and detailed single-case studies by offering a thorough analysis of development projects to identify the factors that are also applicable to similar initiatives in comparable contexts. Empirically, it focuses on two health initiatives, both implemented in the Kyrgyz Republic, a country pursuing a sector-wide approach to health aid. Unique primary material provides insights into a geographic region that is mostly neglected, and will be of interest to students and researchers of social policy, development studies, international health and those focusing on the post-Soviet region and Central Asia. Gulnaz Isabekova is a Researcher at the Research Center for East European Studies at the University of Bremen, Germany. Before joining the CRC 1342 "Global Dynamics of Social Policy," she participated in the MSCA ITN "Around the Caspian." Gulnaz received her Ph.D. from the Bremen International Graduate School of Social Sciences.